Early dynamic changes to monocytes following major surgery are associated with subsequent infections - Snow, Timothy Arthur Chandos; Waller, Alessia V.; Loye, Richard; Ryckaert, Francis; Cesar, Antonio; Saleem, Naveed; Roy, Rudra; Whittle, John; Al-Hindawi, Ahmed; Das, Abhishek; Singer, Mervyn; Brealey, David; et al. (Frontiers in Immunology, 2024)
Background: Post-operative infections are a common cause of morbidity following major surgery. Little is understood about how major surgery perturbs immune function leading to heightened risk of subsequent infection. Through analysis of paired blood samples obtained immediately before and 24 hours following surgery, we evaluated changes in circulating immune cell phenotype and function across the first 24 hours, to identify early immune changes associated with subsequent infection. Methods: We conducted a prospective observational study of adult patients undergoing major elective gastrointestinal, gynaecological or maxillofacial surgery requiring planned admission to the post-anaesthetic care unit. Patients were followed up to hospital discharge or death. Outcome data collected included mortality, length of stay, unplanned Intensive Care Unit admission, and post-operative infections (using the standardized endpoints in perioperative medicine – core outcome measures for perioperative and anaesthetic care (StEP-COMPAC) criteria). Peripheral blood mononuclear cells (PBMC) were isolated prior-to and 24 hours following surgery from which cellular immune traits including activation and functional status were assessed by multi-parameter flow cytometry and serum immune analytes compared by ELISA. Results: 48 patients were recruited, 26 (54%) of whom developed a post-operative infection. We observed reduced baseline pre- and post-operative monocyte CXCR4 and CD80 expression (chemokine receptors and co-stimulation markers respectively) in patients who subsequently developed an infection as well as a profound and selective post-operative increase in CD4+ lymphocyte IL-7 receptor expression in the infection group only. Higher post-operative monocyte count was significantly associated with the development of post-operative infection (False Discovery Rate < 1%; adjusted p value =0.001) with an area under the receiver operating characteristic curve of 0.84 (p<0.0001). Conclusion: Lower monocyte chemotaxis markers, higher post-operative circulating monocyte counts, and reduced co-stimulatory signals are associated with subsequent post-operative infections. Identifying the underlying mechanisms and therapeutics to reverse defects in immune cell function require further exploration.